2016
DOI: 10.31195/ejejfs.258624
|View full text |Cite
|
Sign up to set email alerts
|

Some orthotropic mechanical properties of Sessile oak (Quercus petrea) as influenced by moisture content

Abstract: In this study, the influence of moisture content on some orthotropic mechanical properties of sessile oak which is one of the most important wood species grown in Turkey and common in the furniture industry have been investigated. The properties studied include Young's modulus, Poisson's ratios and compression strength of oak wood in three anatomical directions. These properties are important input parameters for three dimensional modeling of mechanical behavior in advanced computer programs such as finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Data from the study of Jiang et al [29] suggested the ratio was 20.39:1.39:1 of Chinese fir wood. The ratio in the study of Güntekin et al [35] was 8.5:1.6:1 of sessile oak wood. Variations in wood species or measurement methods could cause differences in results, but all above previous studies hold the same magnitude as the results in this study approximately.…”
Section: Compressive Elastic Contents Of Beech Wood With Different Mo...mentioning
confidence: 80%
“…Data from the study of Jiang et al [29] suggested the ratio was 20.39:1.39:1 of Chinese fir wood. The ratio in the study of Güntekin et al [35] was 8.5:1.6:1 of sessile oak wood. Variations in wood species or measurement methods could cause differences in results, but all above previous studies hold the same magnitude as the results in this study approximately.…”
Section: Compressive Elastic Contents Of Beech Wood With Different Mo...mentioning
confidence: 80%
“…These values are lower than those found in literature, although values in literature vary substantially [26][27][28]. This is potentially due to the fact that in this case, the wood is completely saturated, whereas values in literature are based on a lower water content [27].…”
Section: Prototype Materials Propertiesmentioning
confidence: 73%
“…The physical parameters to be determined are obtained with the help of mathematical formulas that link these quantities, some of which are also presented in this thesis. The method of measuring the speed of ultrasound in materials is standardized in ASTM E 494 [16][17][18]. The aim of the paper was to study different types of wood species using the US method.…”
Section: Introductionmentioning
confidence: 99%